Influence Factors on Stress Distribution of Electric Furnace Roof - Jia Liu (Sensors & Transducers, 2013)
Electric furnace roof is an important device for electric steel making, whose heat preservation performance and life-span have a direct impact on the economic benefits of iron and steel enterprise. This paper investigates the effect between the stress level of electric furnace roof and the material parameters. Research indicates that they have a trend to change in the same direction.